Discovery of a solvent effect preventing quantitative profiling by matrix‐assisted laser desorption/ionization and its treatment. (28th December 2015) - Park, Kyung Man; Moon, Jeong Hee; Kim, Jae Hyung; Song, Un Tak; Lee, Seong Hoon; Kim, Myung Soo
Abstract : Rationale: In analyte profiling by matrix‐assisted laser desorption/ionization (MALDI), drawing a quantitative profile map is an outstanding problem. Recently, we developed a method to quantify an analyte by MALDI, which is needed to solve the problem. Another requirement for quantitative profiling is the quantitative sample‐to‐matrix analyte transfer, which is investigated in this work. Methods: MALDI‐time‐of‐flight (TOF) spectra were acquired for samples produced by two methods. In one, a sample solution containing a matrix and an analyte was loaded with a pipet and dried. In the other, a sample was prepared by a consecutive process, i.e., loading‐drying of an analyte solution followed by that of a matrix solution. Two different micro‐spotters were used in the second method. Various mixtures of organic solvents with water were used to prepare matrix solutions. Results: The organic solvent, matrix, and analyte used in the study did not affect the analyte transfer efficiency, whereas it improved as the water content in the solvent increased. It also improved as the liquid droplet emitted by a micro‐spotter got larger. Use of a more polar solvent or a larger droplet increases the contact time between a solution droplet and the sample surface, which seems to be responsible for the improvement in the transfer efficiency. Conclusions: Sample‐to‐matrix analyte transfer occurred efficiently when polar solvents and/or large liquid droplets were used to produce solid samples for MALDI profiling with a micro‐spotter. A long contact time between the sample surface and a matrix solution droplet is one of the requirements for quantitative profiling. Copyright © 2015 John Wiley & Sons, Ltd.